Self-assembly of Di-guanine peptide nucleic acid amphiphiles into fractal patterns - Abraham, Jancy N.; Pawar, Prabhakar; Kootteri, Dilna K. (ChemistrySelect, 2019)
Peptide nucleic acids (PNAs) amphiphiles have been reported to assemble into different nanostructures; however, there is immense untapped potential to control their supramolecular assemblies by altering their lipid chain. Here, we functionalized di-guanine PNA with various hydrophobic appendages, namely dodecyl, p-dodecylbenzoyl and pentadecyl phenol groups, to investigate the effect of aromatic linkers, long alkyl and alkoxyl substituents on hierarchical self-assembly of di-guanine PNA. Systematic electron microscopy and atomic force microscopy studies revealed that while all three derivatives of di-guanine-PNA formed nanospheres, only nanospheres of dodecylamide and pentadecyl phenol derivatives matured into nanorods, these later formed higher order fractal assemblies. Furthermore, we observed that inclusion of a positively charged lysine at the C-terminus prevented fractal assembly, possibly due to electrostatic repulsion between the head groups. Thus, the findings of the present work might guide rational design of PNA amphiphiles to obtain specific self-assembled morphology.
Keywords: Fractal pattern; Guanine; pentadecylphenol; Peptide nucleic acid; Self-assembly

Injectabledextran-fluorenylmethoxycarbonylphenylalanine composite hydrogels with improved mechanical properties - Abraham, Jancy N.; Joseph, Seena; Trivedi, Rishabh; Karle, Mrunal (Polymer International, 2021)
Low molecular weight hydrogels are recently gaining importance owing to their applications in material sciences and biology. A new class of composite hydrogel was developed using polysaccharides such as dextran and fluorenylmethoxycarbonyl phenylalanine (FmocF) in a phosphate buffer. The molecular weight and concentration of the dextran were varied to obtain rigid but injectable hydrogels without using other crosslinking agents. From the different molecular weights of dextran studied (5k, 40k and 70k), a combination of FmocF (0.6% w/v) and dextran 40k (0.012% w/v) composite gels yielded a maximum value of storage modulus of approximately 1500 Pa, which is 3.5 times higher than the storage modulus of pure FmocF gels. Scanning electron microscopy of FmocF/dextran composite gels revealed highly tangled fibrous structures with dense branches and lower fiber diameter compared to pure FmocF gels. The high-intensity hydrogen-bonded N-H peak in the infrared spectra showed enhanced hydrogen bonding in FmocF/dextran composite gels compared to pure FmocF gels. The dextran acts as an impurity in the process of fibrillation, leading to a crystallographic mismatch, and densely packed thin fibers are formed. These gels exhibited gel to sol and sol to gel conversion with temperature or external stress and showed injectable behavior. (c) 2020 Society of Industrial Chemistry
Keywords: Dextran; Fmoc-Phe; hydrogels; injectable gels; Rheology